IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) PERGURUAN TINGGI DAN IMPLIKASINYA PADA INTAKE PERGURUAN TINGGI SWASTA DI BALI - Putu Novia Hapsari Ardianti; Ni Luh Putu Sandrya Dewi (Juara: Jurnal Riset Akuntansi, 2018)
The concept of implementation of Corporate Social Responsibility (CSR) has been applied to the company, although actually every organization, not to mention the college must have social responsibility to the community and environment. For college, the form of social responsibility is formally implicit in Tridharma Perguruan Tinggi in the community. Implementation of wide social responsibility of universities covering the environment, society, business / industry, local government. The main problem in this research is: whether the implementation of CSR affect the Intake of Private Higher Education in Bali. Population in this research is university private that exist in Bali which amounted to 3 universities spread in Denpasar, Badung, and Tabanan. Analysis technique used is logistic regression. Based on the results of the analysis shows that CSR has a positive effect on the Intake of Higher Education. This means that the activity of CSR of Higher Education becomes a separate consideration by the community in choosing a university. The higher the intensity of CSR conducted by universities, the public views that universities have awareness of the community in implementing science and technology so that people will choose the college.